2001
DOI: 10.1128/aem.67.4.1839-1845.2001
|View full text |Cite
|
Sign up to set email alerts
|

Varied Diazotrophies, Morphologies, and Toxicities of Genetically Similar Isolates of Cylindrospermopsis raciborskii (Nostocales, Cyanophyceae) from Northern Australia

Abstract: The potentially toxic freshwater cyanobacterium Cylindrospermopsis raciborskii has become increasingly prevalent in tropical and temperate water bodies worldwide. This paper investigates the effects of different nitrogen sources (NO 3 ؊ , NH 4 ؉ , and omission of a fixed form of nitrogen) on the growth rates, morphologies, and cylindrospermopsin ( ؉ and the statistically significant increase in vegetative cell length (nitrogen depleted < NO 3 ؊ < NH 4 ؉ ). The morphological changes induced by different nitroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
118
7
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(138 citation statements)
references
References 30 publications
(29 reference statements)
6
118
7
1
Order By: Relevance
“…Our results showed that under N-source starvation, monocultures of P. agardhii were unable to grow when NH 4 + or NO 3 x was depleted (i.e., m max = 0), whereas the growth of C. raciborskii seemed unaffected under NH 4 + and/or NO 3 x depletion and low concentration. The growth curves (IVF) recorded here, tend to suggest that C. raciborskii had a higher affinity for NH 4 + , as previously reported in Saker and Neilan (2001) and Kokocinski et al (2010) and other studies, who found that C. raciborskii grew faster when N was supplied in the form of ammonia, followed by nitrate, and then urea. In contrast, P. agardhii exhibited a clear preference for NO 3…”
Section: Discussionsupporting
confidence: 63%
“…Our results showed that under N-source starvation, monocultures of P. agardhii were unable to grow when NH 4 + or NO 3 x was depleted (i.e., m max = 0), whereas the growth of C. raciborskii seemed unaffected under NH 4 + and/or NO 3 x depletion and low concentration. The growth curves (IVF) recorded here, tend to suggest that C. raciborskii had a higher affinity for NH 4 + , as previously reported in Saker and Neilan (2001) and Kokocinski et al (2010) and other studies, who found that C. raciborskii grew faster when N was supplied in the form of ammonia, followed by nitrate, and then urea. In contrast, P. agardhii exhibited a clear preference for NO 3…”
Section: Discussionsupporting
confidence: 63%
“…Isto se deve ao fato do nitrogênio nunca ser limitante no lago, sobretudo o íon amônio (tabela 2) que é a forma preferencial de absorção do nitrogênio (Saker & Neilan 2001). Desta forma, não há necessidade de gastos energéticos para formação de heterocitos.…”
Section: Discussionunclassified
“…These findings raise the question of whether C. curvispora, R. curvata and R. mediterranea can be regarded as separate species or are most likely just rare morphotypes of C. raciborskii. Strains of Cylindrospermopsis and Raphidiopsis from Australia, Brazil, China, Japan and Thailand produce CYN, STXs or ATX (Hawkins et al 1997;Saker and Neilan 2001;Li et al 2001;Namikoshi et al 2003;Soto-Liebe et al 2010). However, all the Cylindrospermopsis and Raphidiopsis strains isolated from Hartbeespoort Dam tested negative for production of cyanotoxins and their encoding genes.…”
Section: R Curvata From Hartbeespoort Dam Than To Cylindrospermopsismentioning
confidence: 96%